Changes in antibiotic concentrations and antibiotic resistome during commercial composting of animal manures. (December 2016) - Xie, Wan-Ying; Yang, Xin-Ping; Li, Qian; Wu, Long-Hua; Shen, Qi-Rong; Zhao, Fang-Jie
Abstract: The over-use of antibiotics in animal husbandry in China and the concomitant enhanced selection of antibiotic resistance genes (ARGs) in animal manures are of serious concern. Thermophilic composting is an effective way of reducing hazards in organic wastes. However, its effectiveness in antibiotic degradation and ARG reduction in commercial operations remains unclear. In the present study, we determined the concentrations of 15 common veterinary antibiotics and the abundances of 213 ARGs and 10 marker genes for mobile genetic elements (MGEs) in commercial composts made from cattle, poultry and swine manures in Eastern China. High concentrations of fluoroquinolones were found in the poultry and swine composts, suggesting insufficient removal of these antibiotics by commercial thermophilic composting. Total ARGs in the cattle and poultry manures were as high as 1.9 and 5.5 copies per bacterial cell, respectively. After thermophilic composting, the ARG abundance in the mature compost decreased to 9.6% and 31.7% of that in the cattle and poultry manure, respectively. However, some ARGs (e.g. aadA, aadA2, qacEΔ1, tetL ) and MGE marker genes (e.g. cintI-1, intI-1 and tnpA-04 ) were persistent with high abundance in the composts. The antibiotics that were detected at high levels in the composts (e.g. norfloxacin and ofloxacin) might have posed a selection pressure on ARGs. MGE marker genes were found to correlate closely with ARGs at the levels of individual gene, resistance class and total abundance, suggesting that MGEs and ARGs are closely associated in their persistence in the composts under antibiotic selection. Our research shows potential disseminations of antibiotics and ARGs via compost utilization. Graphical abstract: Highlights: High levels of fluoroquinolones found in poultry or swine manure-based composts. Industrial-scale thermophilic composting reduced ARG abundance substantially. Multiple ARGs on integron cassettes were prevalent in manures and composts. MGEs and antibiotics played important parts in ARG proliferation and persistence. Abstract : Commercial thermophilic composting was inadequate in reducing antibiotic residues and antibiotic resistance genes.